The Effect Of Perceived Value, Perceived Satisfaction, And Perceived Quality On Customer Loyalty At KKV Retail Stores In Yogyakarta - Firman Alsidiq Asmunir; Albari (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of perceived value, perceived satisfaction, and perceived quality on customer loyalty at KKV retail stores in Yogyakarta, using a sample of 150 respondents who have made purchases more than three times. A quantitative approach was used in this study with the SEM-PLS analysis tool. The results showed that all independent variables, namely perceived value, perceived satisfaction, and perceived quality, had a positive and significant effect on customer loyalty. This finding provides important managerial implications, namely that retail companies need to improve perceived value, service quality, and customer satisfaction to strengthen customer loyalty in the face of increasingly fierce retail industry competition.